The archaeology of medieval towns : case studies from Japan and Europe - Kaner, Simon,; Ayers, Brian,; Pearson, Richard J.,; Wrenn, Oscar, (Comparative and global perspectives on Japanese archaeology., 2020)
In recent years, major new archaeological discoveries have redefined the development of towns and cities in the Japanese archipelago. The uncovering of the plans of major port towns such as Sakai, Kusado Sengen and Ichijodani, and the revealing of early phases in the development of cities such as Kamakura and Hakata provide an important new resource in understanding the cultural and economic processes which shaped medieval Japan. This fully illustrated book provides a sampler of these findings for a western audience.